Reduced Port Laparoscopic Surgery - Mori, Toshiyuki; Dapri, Giovanni (Springer Japan : Imprint: Springer, 2014)
Reduced port laparoscopic surgery is a fast-developing topic for the laparoscopic surgeon, with the emergence of a number of new techniques as well as new instruments. Edited by surgeons who have pioneered the single-incision approach, this volume provides extensive information for the beginning surgeon, examining different operation techniques and covering the advantages and pitfalls of reduced port laparoscopic surgery. In addition, the text provides the foundation for new ideas to further develop skills for the advanced laparoscopic surgeon.